Gorgona, Baudó and Darién (Biogeographic Chocó, Colombia): model ecoregions for coastal stream ecology studies - Blanco, Juan F. (2014)
This paper summarizes the available information on the geology, hydrology, and biota of coastal streams located in the Gorgona National Natural Park (GNNP), and the Baudó and Darién ecoregions within the Biogeographic Chocó (Colombia). Despite of the scant number of studies, we hypothesized that these streams are consistent with the typology observed in volcanic oceanic islands in the Caribbean and the Pacific that do not conform to the tenets of the River Continuum Concept. Coastal streams in the Biogeographic Chocó are short (100-101km) and steep and waterfalls and cascades are frequent due to tectonic origin. Step-and-pool sequences are common in montane reaches, while cobble-bed glides and riffles dominate in coastal plain reaches. Flow regimes are flashy in Pacific drainages (annual rainfall: <7000mm), but seasonally dry in the Caribbean drainages (<3500mm). Therefore, floods and droughts are important drivers of communities and ecosystem processes. Canopies are closed in low-order streams discharging directly to the ocean, thus contributing large amounts of litter. Diadromous fish and shrimp dominate consumer assemblages and various species are shared with streams in the Central America and the Antilles. These species play ecological roles probably equivalent to those found in other regions. These coastal streams are unique in terms of the number of primary freshwater fishes found (some endemics), and the functionally absence of diadromous gastropods. Rev. Biol. Trop. 62 (Suppl. 1): 43-64. Epub 2014 February 01.